The effect of temperature and photoperiod on the digestive physiology of the South African abalone Haliotis midae - Dixon, Mark Geoffrey (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1992)
Inadequate information of the nutritive physiology and the dietary requirements of abalone are the principle factors that currently limit the development of a formulated feed for the commercial culture of Haliotis midae. The need to develop a method to determine apparent digestibility co-efficient's for abalone in order to facilitate further applied nutritional research was identified. Animals between 50 and 80 mm were collected from natural stocks along the east Cape coast of South Africa at Port Alfred and Great Fish point, and acclimated to laboratory conditions. Initial trials demonstrated that H. midae accepted and preferred a semi-purified diet to the seaweed Plocamium corallorhiza, one of the main components of it's natural diet. A technique of determining apparent digestibility co-efficient's (ADC) using the indirect method with chromic oxide as an inert marker was developed. Digestibility trials yielded higher dry matter (DMADC) and crude protein apparent digestibility co-efficient's (CPADC) for the semi-purified diet than for two species of algae, Gelidium amanzii and P. corallorhiza (83.7% and 95.6%, 70.7% and 80.0%, and 29.9% and 57.3% respectively). The ability of the animals to utilize terrestrial animal and plant ingredients efficiently makes it feasible to use conventional feed ingredients in formulated feeds for H. midae. Trials to determine the effect of different temperatures (15°C, 18°C and 22°C) on DMADC and CPADC of the semipurified diet showed that peak digestibility occurred at 18°C. There was also a positive relationship between temperature and consumption rate. Although no enzyme studies with H. midae have been conducted, the peak ADC's at 18°C is attributed to an increase in enzyme activity at this temperature. Transit time, an inverse function of temperature and consumption, is considered to be responsible for the decrease in the ADC' s at 22°C in conjunction with a possible decrease in enzyme activity at this temperature. A photoperiod trial to investigate the effect of darkness on DMADC and CPADC of the semi-purified diet revealed that digestive efficiency decreased with increasing hours of darkness. There was also a positive relationship between duration of darkness and the rate of consumption. The decrease in ADC's is attributed to decreased transit times as the duration of darkness increased . The contribution of this project to the understanding of abalone nutrition, the development of a formulated abalone feed and systems design for abalone farms is discussed.
Keywords: Abalone culture; Gastropoda -- Physiology; Gastropoda -- Food; Abalones -- South Africa